Pandeiro de náilon: as técnicas de Oswaldinho da Cuíca, Ivison Santos e Pimpa - Ferreira, Gustavo Surian [UNESP] (2016)
The main goal of this work is to analyze some of the different styles in the execution of the pandeiro with synthetic skin. In this way, were interviewed important percussionists of Brazilian music, in special of Samba and Forró, who live in the city of São Paulo. The chose of who to interview happened due the place of feature that these people have in the percussion's world, due how close they are with the theme and due the self style of play pandeiro. In the end of the chambers there is a transcription of a solo or rhythm pattern, that with the reporting about pandeiro's technique and how to get resistance could help the student play his instrument in a conscious way, without excess of motions. Moreover,due to the scarcity of material that addresses this issue, we intend to provide written material focused on this theme, since the few books published on pandeiro focus on the pandeiro with goat skin